The contribution of the flipped learning environment to value perception and controllability of classroom activities as antecedents of learners’ anxiety: A control-value approach - Liu, Li (Frontiers in psychology, 2022)
Students enrolled in tertiary education encounter multiple challenges, which prevent them from being proficient. One of these challenges is anxiety which is a common achievement emotion that impacts many students. Anxiety may prevent learning and may be negatively related to learning due to the negative values of classroom activities and their low controllability. As a result, obtaining more research evidence on anxiety plays an important role in allowing learners to develop the skills they need in different types of technology-based environments such as Flipped Learning (FL). With the prevalence of Internet usage, FL is gaining increasing popularity among higher education individuals. The FL approach is an important model for modifying teaching, cultivating enthusiasm, and interaction, and developing educational presentations in student-focused learning circumstances. The potential affordances of the FL environment might place learners in more positive states of control and value appraisals than the environment of conventional classes, which can lead to the removal of negative emotions such as anxiety. Given the benefits of FL and the potential affordances of its environment, the purpose of this conceptual study is to argue how the inherent affordances of the FL environment can contribute to the controllability and positive values of classroom activities reducing learners’ anxiety in light of control-value theory.